Polymyalgia Rheumatica Revealing a Lymphoma: A Two-Case Report - Frank Verhoeven; Xavier Guillot; Mickaël Chouk; Clément Prati; Daniel Wendling (Case Reports in Rheumatology)
Introduction. Polymyalgia rheumatica (PMR) is one of the most common inflammatory rheumatism types in elderly population. The link between cancer and PMR is a matter of debate. Methods. We report two cases of PMR leading to the diagnosis of lymphoma and the growing interest of PET-TDM in this indication. Results. A 84-year-old man known for idiopathic neutropenia presented an inflammatory arthromyalgia of the limb girdle since one month. Blood exams highlighted the presence of a monoclonal B cell clone. Bone marrow concluded to a B cell lymphoma of the marginal zone. He was successfully treated with 0.3 mg/kg/d of prednisone, and response was sustained after 6 months. A 73-year-old man known for prostatic neoplasia in remission for 5 years presented arthromyalgia of the limb girdle since one month. PET-CT revealed bursitis of the hips and the shoulders, no prostatic cancer recurrence, and a metabolically active iliac lymphadenopathy whose pathologic exam concluded to a low grade follicular lymphoma. He was successfully treated with 0.3 mg/kg/d of prednisone. Conclusion. These observations may imply that lymphoma is sometimes already present when PMR is diagnosed and PET-CT is a useful tool in the initial assessment of PMR to avoid missing neoplasia.